A simplified cost-effective method for area-wide testing of trypanocidal drug sensitivity of T. congolense in mice - Geerts, S.; Ndung'u, J.M.; Murilla, G.; Mbwambo, H.; Sinyangwe, L.; Machila, N.; Delespaux, V.; Brandt, J.; Peregrine, A.S.; McDermott, John J.; Holmes, P.H.; Eisler, M.C. (OAU/STRC, 2001)
Testing of trypanocidal drug sensitivity in stabilates of pathogenic trypanosomes derived from cattle continues to be problematic, in spite of Development of in vitro techniques, since these are generally complicated and costly for the resources available in developing country laboratories. Furthermore, such assays are unable to characterise rapidly large numbers of trypanosome populations. Many populations of T congolense and T brucei may be isolated directly by inoculation of mice with blood of infected cattle, without the need for carrying liquid nitrogen to the field Mice may then be used for testing trypanocidal drug sensitivity. Classically this involves using multiple drug doses to determine the dose required to cure 50% of animals (CD50), requiring at least 30 mice per drug. However, many laboratories lack the resources required to maintain a mouse colony large enough to test significant numbers of isolates by this method. A simplified protocol for trypanocidal drug-sensitivity testing using just 3 doses for either isometamidium (0.1, 1.0 and 10 mg1kg b.w.) or diminazene (1, 20 and 40 mg/kg b.w.) was evaluated. This method requires at least 15 mice per drug and represents a significant reduction over full CD50 testing. The method showed clear differences in the level of drug sensitivity of T congolense populations from different areas of Kenya, Tanzania, and Zambia. Finally, an even more simplified protocol was developed on the basis of results obtained with the three-dose protocol, using just a single dose of each drug; 1.0 mg/kg b.w. for isometamidium, and 20 mg/kg b.w. for diminazene. This method requires just 6 mice per drug, plus controls. While this method is not able to provide definitive information on the level of drug sensitivity of individual stabilates, it provides a cost-effective means of characterising the resistance phenotype of large numbers of trypanosome populations in a given area. The method is not however applicable to T vivax infections, which are rarely infective for mice.